Social Psychology and Human Rights: the intervention of psychology in the face of military dictatorship and current manifestations in Brazil - Ferrazza, Daniele Andrade; Costa, Juliana Camargo; Oliveira, Patrícia Alves (Revista de Psicologia da IMED, 2014)
This work aims to analyze the acting and positioning of psychology professionals in respect to social movements both during periods of repression of the military dictatorship as in the recent Brazilian manifestations that accompanied the movement of "Free Pass". For this study the area of Social Psychology, was used as a methodological procedure bibliographic research literature and current news reports on the subject. We conclude that although there are opportunities to participate in psychology spaces, complaint against the violation of human rights and debates for materialisation of rights and citizenship conquest, as in current manifestations, and also there is difficulty filling those spaces marked by many professionals for corporate trend would be accommodated in their own professional status only standying up to confrontation exercising to ensure the stability and consolidation of the social image of profession.